Examining New Product Development Speed and Team Work Quality Relationship: Evidence from Telecom Industry - Asmat-Nizam Abdul-Talib; Turki Abdullah Alanazi; Hasbullah Ashari (International Journal of Supply Chain Management, 2019)
Although prior research has suggested that team work quality and internal market orientation can affect new product development (NPD) speed in a positive direction, however relatively little research has examined the incremental validity of team work quality to NPD speed after controlling for internal market orientation. To address this theoretical gap in marketing literature, the present study attempts to examine whether the dimensions of team work quality account for incremental variance in NPD speed, after controlling for the dimensions of internal market orientation.Â Using a random sampling, a total of 149 members of NPD teams in Saudi telecommunications firms responded to measures of each construct.Â Hierarchical multiple regression analysis was performed to access the incremental validity. Overall results suggest that cohesion accounted for a significant amount of variance relative to coordination, balance of member contribution, efforts, communication, mutual support and other dimensions of internal market orientation in the prediction of NPD speed.